Wind Tunnel Measurements of a Multibladed Horizontal-Axis Small Wind Turbine - Porto,Heitor Andrade (2021)
ABSTRACT This work experimentally investigates the effects that a different number of blades, three and five, has in the dynamic torque, acceleration, and power performance of a horizontal-axis small wind turbine. It presents the methodology used for calculating the temporal behavior of the aerodynamic torque generated by the blades during their acceleration phase. The tests were performed in an open section wind tunnel of 1.0 × 0.8 m. The model was produced by additive manufacturing and had two possible assemblies, with three and five blades. An in-line dynamic torque meter acquired the torque and angular speed data, and a National Instruments USB-6009 device processed the signal. The resistive torques were calculated by spin-down tests. The tests were executed at a wind speed of 10 m·s–1. The measurements displayed the five blades assembly having improved performance compared to the three blades: a higher static torque, which resulted in shorter stating time, and a power coefficient 39% higher.